2021
DOI: 10.3168/jds.2020-19214
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of body weight at first calving with milk yield and herd life

Abstract: The objectives of this study were to investigate the association of body weight (BW) at first calving (BWFC) and maturity rate (MR; BWFC as a percentage of mature BW) with first-lactation 305-d milk yield (FLMY), milk yield (MY) in the 24 mo following first calving (24MMY), herd life, and BW change (BWC) through the first month of lactation in Holstein heifers. We retrieved daily milk production records and daily BW records from AfiFarm (S. A. E. Afikim, Kibbutz Afikim, Israel). The data set included daily rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The excess fat gain and condition for heifers fed HE can have negative consequences around calving such as increased calving difficulty (Hoffman et al, 1996). Recent work by Han et al (2021) found that heifers which were heavier at first calving and likely with greater condition had greater first-lactation production, however, were culled from the herd at an earlier age due to greater negative energy balance and metabolic disease postcalving, and reduced reproduction. These results confirm the validity of the ultrasound technique, as the rump fat depth followed closely the observed final BCS.…”
Section: Heifer Growth and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The excess fat gain and condition for heifers fed HE can have negative consequences around calving such as increased calving difficulty (Hoffman et al, 1996). Recent work by Han et al (2021) found that heifers which were heavier at first calving and likely with greater condition had greater first-lactation production, however, were culled from the herd at an earlier age due to greater negative energy balance and metabolic disease postcalving, and reduced reproduction. These results confirm the validity of the ultrasound technique, as the rump fat depth followed closely the observed final BCS.…”
Section: Heifer Growth and Performancementioning
confidence: 99%
“…Delayed breeding or poor conception allowed heifers to gain additional weight and condition before calving; thus, the reproduction and nutrition programs both play important roles in heifer management. In addition, a study by Han et al (2021) found that heifers with higher BW (>570 kg) and maturity rate (>80% of mature BW at first calving) after first calving had somewhat higher first-lactation milk yields, but did not have greater milk yield through the first 24 mo after first calving. Heavier first-lactation cows also had greater BW loss during the first month of lactation, greater culling risks, and less longevity.…”
Section: Lactation Performancementioning
confidence: 99%
“…After fully transitioning to solid feed, there are many different strategies that can be employed to ensure proper development during the next crucial stages of life (i.e., puberty, pregnancy, calving). The established guidelines for heifers in our industry is to target first calving between 22 and 24 mo at 0.82 × mature BW (Van Amburgh et al, 2019); however, recent data suggests that a target of 0.73 to 0.77 × mature BW increases milk production in first lactation without compromising long-term production (Han et al, 2021). Certainly, heifer rearing targets and requirements are not well understood during the prepubertal and postpubertal phases and may be influenced by nutrition earlier in life.…”
Section: Prepubertal and Postpubertal Phasesmentioning
confidence: 99%
“…Інтенсивність росту телиць залежить також від генотипових чинників, а також тісно пов'язана з рівнем молочної продуктивності (Laduka et al, 2010;Romanenko et al, 2010;Poslavska et al, 2016b;Fedorovych et al, 2016). Багатьма вченими (Gil et al, 2018;Polupan & Siriak, 2019, Ferenz et al, 2018Han et al, 2021) доведено, що між інтенсивністю росту телиць та їхньою майбутньою молочною продуктивністю існує кореляційна залежність.…”
Section: вступunclassified